PENGETAHUAN PEREMPUAN DAN AKUNTABILITAS DANA DESA: PENGGERAK EKONOMI KREATIF PERDESAAN DI RIMO MUNGKUR - Awaludin (Penerbit Lafadz Jaya, 2025)
This study explores the contribution of women’s knowledge in promoting accountability in village fund management while simultaneously fostering the development of the creative economy in Rimo Mungkur Village. Using a qualitative approach with interviews, observations, and documentation, the study finds that women’s involvement goes beyond being mere beneficiaries; they play a significant role as social oversight agents in ensuring transparency and accountability of village funds. The local knowledge possessed by women is utilized to identify community priority needs, ensure program alignment with local conditions, and encourage more participatory governance practices. Furthermore, rural women serve as driving forces in developing creative economic activities based on local potentials, such as agricultural product processing, handicrafts, and home-based micro-enterprises. These activities not only enhance household income but also strengthen village economic independence. The findings demonstrate that the integration of women’s knowledge, village fund accountability, and creative economy development forms a more inclusive and sustainable rural development ecosystem. This study is relevant to rural economy studies, emphasizing the importance of social actors’ participation in achieving fair, transparent, and empowerment-oriented governance.